Mathematical analysis of blood flow through an arterial segment with time‐dependent stenosis - Misra, Jagadis Chandra; Adhikary, Sudi D.; Shit, Gopal Chandra (Mathematical Modelling and Analysis, 2008)
A mathematical model is developed here with an aim to study the pulsatile flow of blood through an arterial segment having a time‐dependent stenosis. Blood is considered to consist of a core layer where erythrocytes are concentrated and a peripheral plasma layer that is free from erythrocytes. The plasma layer is taken to behave as a Newtonian fluid, while the core layer is represented by as a Casson fluid (non‐Newtonian) model. The pulsatile flow is analyzed by considering a periodic pressure gradient, which is a function of time. A perturbation analysis is employed to solve the governing differential equations by taking the Womersley frequency parameter to be small (α